A Large Simulation Set of Geomagnetic Storms—Can Simulations Predict Ground Magnetometer Station Observations of Magnetic Field Perturbations? - Q. Al Shidi; T. Pulkkinen; G. Toth; A. Brenner; S. Zou; J. Gjerloev (Space Weather)
Abstract We use the Space Weather Modeling Framework Geospace configuration to simulate a total of 122 storms from the period 2010–2019. With the focus on the storm main phase, each storm period was run for 54 hr starting from 6 hr prior to the start of the Dst depression. The simulation output of ground magnetic variations, ΔBH in particular, were compared with ground magnetometer station data provided by SuperMAG to statistically assess the Geospace model regional magnetic perturbation prediction performance. Our results show that the regional predictions at mid‐latitudes are quite accurate, but the high‐latitude regional disturbances are still difficult to predict.